Collaboration between Public Sectors and Community Organizations to Inhibit the Insurgencies Occurring in the Unrest Areas in the Southernmost Provinces - Bunnam, Chaleomsak; Rinthaisong, Idsaratt; Songsom, Anuwat (International Journal of Social Sciences and Management, 2017)
The present study purposes to identify the consequences of collaboration between public sectors and community organizations and to study influential factors towards collaboration to inhibit insurgencies in the unrest areas in the southernmost provinces. There were sixteen key informants habituating organizations situated in both rural and urban areas that include leaders, committees, or members who are deployed as representatives of the organizations in the southernmost provinces, and ten people in a focus group. The research instrument was semi - structured interviews. It was found that three phases of collaboration between public sectors and community organizations in the southernmost provinces are: 1) pre-insurgency collaboration in conducting activities and projects due to government policies; 2) insurgent periods collaboration in coordination, following up, and communication; 3) post-insurgency, collaboration in habitation, healing, and assistance. Moreover, influential factors towards collaboration to inhibit insurgencies in the unrest areas in the southernmost provinces, e.g. trustworthiness and communication between public sectors and community organizations, participation in peace processes, community administration, identity expression, and policy appropriateness. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 90-95